Mitochondria’s Role in the Maintenance of Cancer Stem Cells in Glioblastoma - Iranmanesh, Yasaman; Jiang, Biao; Favour, Okoye C.; Dou, Zhangqi; Wu, Jiawei; Li, Jinfan; Sun, Chongran (Frontiers in Oncology, 2021)
Glioblastoma (GBM), one of the deadliest primary brain malignancies, is characterized by a high recurrence rate due to its limited response to existing therapeutic strategies such as chemotherapy, radiation therapy, and surgery. Several mechanisms and pathways have been identified to be responsible for GBM therapeutic resistance. Glioblastoma stem cells (GSCs) are known culprits of GBM resistance to therapy. GSCs are characterized by their unique self-renewal, differentiating capacity, and proliferative potential. They form a heterogeneous population of cancer stem cells within the tumor and are further divided into different subpopulations. Their distinct molecular, genetic, dynamic, and metabolic features distinguish them from neural stem cells (NSCs) and differentiated GBM cells. Novel therapeutic strategies targeting GSCs could effectively reduce the tumor-initiating potential, hence, a thorough understanding of mechanisms involved in maintaining GSCs’ stemness cannot be overemphasized. The mitochondrion, a regulator of cellular physiological processes such as autophagy, cellular respiration, reactive oxygen species (ROS) generation, apoptosis, DNA repair, and cell cycle control, has been implicated in various malignancies (for instance, breast, lung, and prostate cancer). Besides, the role of mitochondria in GBM has been extensively studied. For example, when stressors, such as irradiation and hypoxia are present, GSCs utilize specific cytoprotective mechanisms like the activation of mitochondrial stress pathways to survive the harsh environment. Proliferating GBM cells exhibit increased cytoplasmic glycolysis in comparison to terminally differentiated GBM cells and quiescent GSCs that rely more on oxidative phosphorylation (OXPHOS). Furthermore, the Warburg effect, which is characterized by increased tumor cell glycolysis and decreased mitochondrial metabolism in the presence of oxygen, has been observed in GBM. Herein, we highlight the importance of mitochondria in the maintenance of GSCs.